COMMUNITY SERVICE EDUCATION OF PRE-ECCLESIASTIC DANGER SIGNS IN PREGNANT WOMEN AT HANA KASIH CLINIC - Leni Agustina; Herlina; Rut Sarah Rotua Nainggolan (Jurnal Masyarakat Indonesia (Jumas), 2024)
Preeclampsia is one of the leading causes of maternal death characterized by increased blood pressure and proteinuria after 20 weeks of gestation, which if not treated appropriately can lead to fatal complications for both mother and fetus. This community service activity aims to increase the knowledge and awareness of pregnant women and their families about the warning signs of preeclampsia and the importance of early detection. The activity was carried out at the Hana Kasih Clinic on May 23, 2024 by an academic team from STIKes Darmo Medan. The method used is structured educational counseling, which is evaluated using a quantitative design through pre-test and post-test to measure the improvement of participants' understanding. The results of the activity showed a significant increase in pregnant women's understanding of the early symptoms of preeclampsia, the importance of routine blood pressure checks, and quick steps to be taken in emergency situations. In conclusion, structured education about the warning signs of preeclampsia is an effective preventive and promotive strategy to empower pregnant women, increase independence in pregnancy risk management, and support efforts to reduce maternal pain and mortality in the work area of Hana Kasih Clinic.